m2+6/5=11

Simple and best practice solution for m2+6/5=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m2+6/5=11 equation:



m2+6/5=11
We move all terms to the left:
m2+6/5-(11)=0
determiningTheFunctionDomain m2-11+6/5=0
We add all the numbers together, and all the variables
m^2-11+6/5=0
We multiply all the terms by the denominator
m^2*5+6-11*5=0
We add all the numbers together, and all the variables
m^2*5-49=0
Wy multiply elements
5m^2-49=0
a = 5; b = 0; c = -49;
Δ = b2-4ac
Δ = 02-4·5·(-49)
Δ = 980
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$m_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$m_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{980}=\sqrt{196*5}=\sqrt{196}*\sqrt{5}=14\sqrt{5}$
$m_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-14\sqrt{5}}{2*5}=\frac{0-14\sqrt{5}}{10} =-\frac{14\sqrt{5}}{10} =-\frac{7\sqrt{5}}{5} $
$m_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+14\sqrt{5}}{2*5}=\frac{0+14\sqrt{5}}{10} =\frac{14\sqrt{5}}{10} =\frac{7\sqrt{5}}{5} $

See similar equations:

| k=0.04k^2 | | 0.2k=0.5k^2 | | 4(2x-5)=2(3x+7) | | 3x^2+13x+20=0 | | 30/d=60 | | 2/4(2x+5)=6 | | 2x-x+1-4=-3+x | | 4x+2(97)=5(97)-2x | | 1/4x^2+3x-5=0 | | 10/x=13/17 | | 12.3^2x+13.3^x-7=0 | | b/(-1/4)b=21 | | 60-2x+81+x=180 | | 12.3^(2x)+13.3^x-7=0 | | 20.04+x=14.3 | | 1800=n+2*180 | | 140n=(2-n)*180 | | 140=(2-n)*180 | | x=x/12+30 | | y=0.08*7496+7400 | | 600=0.08x+7400 | | 2x^2+1=3x^2+5 | | 6x^2+4=5x^2+9 | | 4x-11+x-9=90 | | X-2(13+7x)=11 | | 2(10x-4)=3(2x+16) | | x*(-12+18)=40 | | 6m+100=40 | | X^2-6x-9+(x-3)(x+4)=0 | | t+24t=12 | | x2+8x+10=30 | | -5-2.5x-19=-4 |

Equations solver categories